Estudo morfo-anatômico da folha e do caule de Piper arboreum Aubl. (Piperaceae) - Souza, Luis A.; Albiero, Adriana L.M.; Almeida, Odair J.G. [UNESP]; Lopes, William A.L.; Mourão, Káthia S.M.; Moscheta, Ismar S. (My University, 2009)
The genus Piper L. includes a great number of medicinal interest species. P. arboreum is frequent in forests of Maringá, Paraná State, Brazil. Its leaves and stem are analyzed morphologic and anatomically, freehand sectioned in cross-section and longitudinal section, and were stained in astra blue and safranin. Petiole and midrib base present 15-20 vascular bundles. The blade is hypostomatic, dorsiventral and shows staurocytic stomatal complex, subepidermis and oil idioblasts. The stem possesses medullary vascular bundles; a typical endodermis is not observed, as it occurs in other Piper species.
Morphological and anatomical study of leaf and stem of Piper arboreum Aubl. (Piperaceae)
Keywords: Anatomy; Leaf; Morphology; Piper arboreum; Piperaceae; Stem